TARGET2 imbalances and the ECB as lender of last resort - Francesco Purificato; Caterina Astarita (International Journal of Financial Studies, 2015)
This paper analyses the issue of the dynamics of the TARGET2 system balances during the sovereign debt crisis, when some countries registered a decisive inflow of the central bank liquidity and others showed an outflow. The dynamics in the TARGET2 are here explained as being due to a fall in the level of confidence in the capacity of the Economic and Monetary Union to survive, rather than to disparities in the level of competitiveness among countries of the Eurozone. This crisis of confidence has to be considered as the consequence of the implicit refusal of the European institutions to create a mechanism working as lender of last resort for the euro area member States; indeed, only when the ECB took this responsibility by launching the Outright Monetary Transactions clear signs of improvement were observed in the sovereign debt crisis.
Keywords: E42; E52; E58; E62; F32; F34; F36; 330; payment system; monetary policy; fiscal policy; financial crisis